The Effect of Sensory Learning Media on the Learning Motivation of Second Grade Elementary School Students (Universitas Pendidikan Indonesia Kampus Cibiru, 2024)
This study aims to explore in depth the impact of sensory learning media on student learning motivation in second grade elementary school. The background of this study stems from the urgent need for innovation in the learning process, especially at the elementary school level, to increase student active participation and interest in learning. The author recognizes that motivation in learning is a key foundation that greatly influences students' overall academic achievement and success. For this study, the author applied a quantitative approach, in which we tested the core hypothesis that the use of interactive and multisensory learning media can engage students' various senses. This study shows that the use of learning media that involves the five senses can increase the learning motivation of second-grade elementary school students. This media makes the learning process more interesting, interactive, and enjoyable so that students are more enthusiastic about participating in learning activities. In addition, the involvement of the five senses helps students understand the material better through direct learning experiences. Therefore, sensory-based learning media can be an effective method to increase student motivation and understanding at the elementary school level. This study is expected to contribute to the development of more effective and innovative learning strategies and serve as a reference for educators in implementing sensory learning media in elementary schools.